Effective Practical Solutions for De-Icing of Automotive Component - Andrea Tinti; Gloria Anna Carallo; Antonio Greco; María Dolores Romero-Sánchez; Luigi Vertuccio; Liberata Guadagno (Nanomaterials, 2022)
Carbon Nanotube (CNTs)-based masterbatches have been mixed with thermoplastic polymers currently used to manufacture automotive components. These mixtures have been tailored to integrate an effective heating function in the materials. The manufacturing method for composite compounding and processing conditions significantly affects the electrical resistivity of the developed materials. The resistivity of the material can be controlled within tight tolerances sufficient to meet automotive requirements. The optimal compounding parameters of the melt process technologies were defined to obtain uniform filler dispersion and distribution. Heating and de-icing tests were performed on sheet specimens with optimized CNT content and electrical conductivity suitable for effective electro-thermal behaviour with low input voltages (≤24 V DC), making them safe for users. Finally, a simplified analytical model of the Joule effect arising from an energy balance of the system under study (heat equation) was developed and validated by comparison with experimental data for use in future development for the purpose of the preliminary design of components in the automotive sector.